Cambio conceptual en los grupos de crecimiento personal - Gil Escudero, Guillermo (Miscelánea Comillas, 2012)
After reviewing what currently are Personal Growth Groups (PGG), theirorigins, characteristics and the studies that evaluate their effectiveness, and theuse of Semantic Differential (SD) as an instrument to measure psychotherapeutic change, the contribution and efficiency of PGG to the change of meaning ofsome main psychological concepts of participants in these groups, are examined through the SD methodology. These changes of meaning are considered as indicators of the emotional, attitudinal and cognitive changes that usually turn outas a result of the participation in such intensive group experiences. Finally,results of participant’s personal satisfaction with the group experience are briefly presented.